Altars of the world - Ayres, Lew, 1908-1996.; Wellspring Media (New York, NY : Wellspring Media, 2003)
Examines the religions of the world, their history, practices commonalities and differences.
The Eastern religions: The wheel of karma (Hinduism) -- Theravada Buddhism (Doctrine of the elders) -- Mahayana Buddhism (The great vehicle) -- Buddhism in Japan -- Shinto -- Guardians of life (the Jains) -- The pillars of Allah: Islam -- The sword and the book: Sikhism -- The flame of Zoroaster -- The Western religions: Children of Abraham: Judaism -- Way of the rugged cross: Christianity -- Roman Catholic -- Eastern Orthodox -- Lutherans -- Presbyterians -- Baptists -- Episcopalians -- The Charismatics -- Methodists.
Lew Ayres, host.
MPAA rating: Not rated.
DVD, Dolby Digital.
Keywords: Religion; Documentary films